Secondary metabolites produced by grapevine strains of Lasiodiplodia theobromae grown at two different temperatures. (4th May 2019) - Félix, Carina; Salvatore, Maria M.; DellaGreca, Marina; Ferreira, Vanessa; Duarte, Ana S.; Salvatore, Francesco; Naviglio, Daniele; Gallo, Monica; Alves, Artur; Esteves, Ana C.; Andolfi, Anna
ABSTRACT: Lasiodiplodia theobromae is a fungal plant pathogen that has been associated with Botryosphaeria dieback of grapevine. Despite several studies on L. theobromae, until now the production of secondary metabolites by strains isolated from grapevines has not been reported. The ability of two strains of L. theobromae isolated from grapevine to produce lipophilic metabolites was studied. Although many typical compounds of low molecular weight were identified from the crude extracts of both strains (e.g., lasiolactols, substituted 2-dihydrofuranones, melleins, jasmonic acid, 3-indolcarboxylic acid, botryodiplodins), (2 R /2 S, 3 S, 4 S )-3- epi -botryodiplodin was isolated for the first time as a natural compound. Furthermore, a comparative study of metabolite production was conducted at 25 and 37 C to understand temperature effects on metabolite profiles. Some metabolites were produced only by one strain (e.g., (3 S, 4 S )-4-acetyl-3-methyl-2-dihydrofuranone produced by LA-SOL3) and others only at a specific temperature (e.g., jasmonic acid at 25 C, botryodiplodins at 37 C). Phytotoxicity and cytotoxicity of pure compounds were evaluated to clarify the influence of lipophilic metabolites on the biological activities of culture filtrates of both strains. The most toxic compound for Vero and 3T3 cells was (2 R /2 S, 3 S, 4 S )-3- epi -botryodiplodin.